DIAUTIS II: A Multi-agent Platform for the Diagnosis of Autism and the Design of Serious Games - El-Alami, Mohamed; El-Khabbazi, Sara; Tahiri , Najoua; Arriaga, Fernando de (Current Overview on Science and Technology Research Vol. 4, 2022)
Autism Spectrum Disorder occurs at an early stage of life and produces significant behavioural imbalances. Available data indicate that autism is growing at an alarming pace. Early diagnosis is important in administering the aids to which it refers, especially those related to learning. DIAUTIS I is a platform aimed at assisting the clinical team, doctors, parents, guardians and schools in the diagnosis of this disease. Its ability to cognitive, fuzzy, and affective computing, along with the ability to learn from experience, gives the multi-agent system many possibilities. One of them is presenting a variety of test collections, assessing the child's test findings, and presenting a final diagnosis of the child's ailment and the seriousness of the disorder. Tests carried out show that DIAUTIS can perform a long series of diagnostic tests reliably and efficiently. DIAUTIS II expanded the possibilities of DIAUTIS I through a methodology for the design of serious games based on four pillars: knowledge, affect, sensory, and pedagogy. The methodology allows DIAUTIS II agents to design games from more than 80 templates, taking into account the child’s background.